Studi Daya Dukung Fondasi Tiang Pada Tanah Lempung Teguh Berdasarkan Pembebanan Kepala Tiang Dan Pergerakan Ujung Tiang Metode T-Z - Firmansyah, Mochamad fikri firmansyah Fikri; Fausta, Rakha; Darjanto, Helmy (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2020)
Developments in the calculation of foundation planning today have produced many methods and formulas for calculating the bearing capacity of foundations, such as the T-Z method, the Tezaghi method, the Mayerhof method, the Tomlison method, and other methods. So the purpose of this study was to determine the bearing capacity from tip movement of the foundation of each load with the T-Z method. The T-Z method explains rationally the mechanism of load transfer using a load transfer function commonly called TZ. In this method the pile foundation will be divided into several segments and the transfer function on each side segment which is a function of the shear strength of the soil and the surface properties of the side pile. From the analysis results of the TZPILE application, the bearing capacity is due to the settlement. At a settlement of 0,0001m; 0.001m; 0.0015m; 0.0025m; and 0.005m get a bearing capacity of 4.31kN; 31.69 kN; 35.6 kN; 43.44 kN; and 60.10kN. And on the reduction of permits on the foundation that occurs according to SNI 8460 - 2017 is 25mm, so the analysis obtained 12mm which still meets the requirements, 12mm get a bearing capacity of 1200kN at the tip of the pile. At a load of 600 kn the head of the pile can be held at a depth 4 meters. And for the maximum bearing capacity of the 18 meter pole, it can whitstand a bearing capacity of 1200 kn.